Pengaruh Kualitas Pelayanan, Kualitas Produk dan Persepsi Harga Terhadap Kepuasan Pelanggan di Restoran Padang Sederhana Cakung - Malvin Raffy Oscar; Rully Arifiansyah (Human Capital Development, 2023)
This study aims to investigate the impact of service quality, product quality, and price perceptions on customer satisfaction at the Simple Padang Restaurant in Cakung. Sampling was carried out using a purposive sampling technique and involved 100 respondents. Hypothesis testing is done by applying path analysis using SPSS software. The results showed that service quality has a positive and significant impact on customer satisfaction; product quality has a significant influence on customer satisfaction; and price perceptions have a positive and significant influence on customer satisfaction.